Seed Inoculation and Foliar Application of Micronutrients Improve the Yield and Quality of Pinto Bean - Mansour Taghvaei; Abdolmajid Nikouei; Mahboubeh Fazaeli; Akbar Hemmati; Andrea Mastinu (Plant-Environment Interactions)
ABSTRACT To investigate the effect of bio‐fertilizer pretreatment and foliar application of the micronutrients zinc and iron on the yield and yield components of pinto beans (Phaseolus vulgaris L.). The experimental treatments included a control, pretreatment with mycorrhizal fungi, pretreatment with rhizobial bacteria, combined pretreatment with mycorrhizal fungi and rhizobial bacteria, and additional combinations of these with foliar applications: mycorrhizal fungi and rhizobial bacteria with iron foliar spray, with zinc foliar spray, and with both iron and zinc foliar sprays. Bio‐fertilizer pretreatment significantly increased all studied traits compared to the control. The combination of seed inoculation with mycorrhizal fungi and rhizobial bacteria, along with iron foliar application, notably enhanced plant height, root colonization, leaf chlorophyll content, antioxidant enzyme activities, and nutrient levels in seeds, including nitrogen, potassium, and iron. However, the foliar application of zinc and iron resulted in reduced phosphorus content in the seeds, with the highest zinc content observed in the treatment combining bio‐fertilizers with zinc foliar spray. The combined bio‐fertilizer and iron foliar treatment achieved the highest grain yield and biological yield. These results indicate that the use of bio‐fertilizers, along with foliar applications of iron and zinc, can effectively enhance the morpho‐physiological characteristics, yield, and quality of pinto beans.